The genetic cause of intellectual deficiency and/or congenital malformations in two parental reciprocal translocation carriers and implications for assisted reproduction - Cheng, Dehua (J Assist Reprod Genet, 2020)
PURPOSE: To elucidate the genetic cause of intellectual deficiency and/or congenital malformations in two parental reciprocal translocation carriers and provide appropriate strategies of assisted reproductive therapy (ART). MATERIALS AND METHODS: Two similar couples having a child with global developmental delay/intellectual disability symptoms attended the Reproductive and Genetic Hospital of CITIC-Xiangya (Changsha, China) in 2017 and 2019, respectively, in order to determine the cause(s) of the conditions affecting their child and to seek ART to have a healthy baby. Both of the healthy couples were not of consanguineous marriage, denied exposure to toxicants, and had no adverse life history. This study was approved by the Institutional Ethics Committee of the Reproductive & Genetic Hospital of CITIC-Xiangya, and written informed consent was obtained from the parents. Genetic diagnoses were performed by karyotype analysis, breakpoint mapping analysis of chromosomal translocation(s), single-nucleotide polymorphism (SNP) microarray analysis, and whole-exome sequencing (WES) for the two children and different appropriate reproductive strategies were performed in the two families. RESULTS: Karyotype analysis revealed that both patients carried parental reciprocal translocations [46,XY,t(7;16)(p13;q24)pat and 46,XY,t(13;17)(q12.3;p11.2)pat, respectively]. Follow-up breakpoint mapping analysis showed no interruption of associated genes, and SNP microarray analysis identified no significant copy number variations (CNVs) in the two patients. Moreover, WES results revealed that patients 1 and 2 harbored candidate compound heterozygous mutations of MCOLN1 [c.195G>C (p.K65N) and c.1061G>A (p.W354*)] and MCPH1 [c.877A>G (p.S293G) and c.1869_1870delAT (p.C624*)], respectively, that were inherited from their parents and not previously reported. Furthermore, the parents of patient 1 obtained 10 embryos during ART cycle, and an embryo of normal karyotype and non-carrier of observed MCOLN1 mutations according to preimplantation genetic testing for structural rearrangement and monogenic defect was successfully transferred, resulting in the birth of a healthy boy. The parents of patient 2 chose to undergo ART with donor sperm to reduce the risk of recurrence. CONCLUSIONS: Systematic genetic diagnosis of two carriers of inherited chromosomal translocations accompanied by clinical phenotypes revealed their cause of disease, which was critical for genetic counseling and further ART for these families. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01986-1) contains supplementary material, which is available to authorized users.